Vancomycin-induced ototoxicity in very-low-birthweight infants. (28th May 2020) - Marissen, Janina; Fortmann, Ingmar; Humberg, Alexander; Rausch, Tanja K; Simon, Arne; Stein, Anja; Schaible, Thomas; Eichhorn, Joachim; Wintgens, Jürgen; Roll, Claudia; Heitmann, Friedhelm; Herting, Egbert; et al.
Abstract: Background: Vancomycin is an extensively used anti-infective drug in neonatal ICUs. However, exposure–toxicity relationships have not been clearly defined. Objectives: To evaluate the risk profile for hearing deficits in vancomycin-exposed very-low-birthweight infants (VLBWI). Methods: In a large cohort study of the German Neonatal Network (GNN; n  =   16 967 VLBWI) we assessed the association of vancomycin treatment and pathological hearing tests at discharge and at 5 year follow-up. We performed audits on vancomycin exposure, drug levels, dose adjustments and exposure to other ototoxic drugs in a subgroup of 1042 vancomycin-treated VLBWI. Results: In the GNN cohort, 28% ( n  =   4739) were exposed to IV vancomycin therapy. In multivariable logistic regression analysis, vancomycin exposure proved to be independently associated with pathological hearing test at discharge (OR 1.18, 95% CI 1.03–1.34, P  =   0.016). Among vancomycin-treated infants, a cumulative vancomycin dose above the upper quartile (>314 mg/kg bodyweight) was associated with pathological hearing test at discharge (OR 2.1, 95% CI 1.21–3.64, P  =   0.009), whereas a vancomycin cumulative dose below the upper quartile was associated with a reduced risk of pathological tone audiometry results at 5 years of age (OR 0.29, 95% CI 0.1–0.8, P  =   0.02, n  =   147). Conclusions: Vancomycin exposure in VLBWI is associated with an increased, dose-dependent risk of pathological hearing test results at discharge and at 5 years of age. Prospective studies on long-term hearing impairment are needed.